Role of Virally Encoded Circular RNAs in the Pathogenicity of Human Oncogenic Viruses - Avilala, Janardhan; Becnel, David; Abdelghani, Ramsy; Nanbo, Asuka; Kahn, Jacob; Li, Li; Lin, Zhen (Frontiers in Microbiology, 2021)
Human oncogenic viruses are a group of important pathogens that etiologically contribute to at least 12% of total cancer cases in the world. As an emerging class of non-linear regulatory RNA molecules, circular RNAs (circRNAs) have gained increasing attention as a crucial player in the regulation of signaling pathways involved in viral infection and oncogenesis. With the assistance of current circRNA enrichment and detection technologies, numerous novel virally-encoded circRNAs (vcircRNAs) have been identified in the human oncogenic viruses, initiating an exciting new era of vcircRNA research. In this review, we discuss the current understanding of the roles of vcircRNAs in the respective viral infection cycles and in virus-associated pathogenesis.